Genome-wide association study identifies five risk loci for pernicious anemia - Triin Laisk (Nature Portfolio, 2021)
Pernicious anemia shows co-incidence with autoimmune disorders, yet the genetic basis for this condition is understudied. Here, the authors perform a genome-wide association study meta-analysis on pernicious anemia, identifying five susceptibility loci that map to genes with known roles in autoimmune disease.